2020
DOI: 10.1093/intqhc/mzaa114
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with the impact of the COVID-19 pandemic on a rapid response team operation in Brazil: Quality in practice

Abstract: Quality problem or issue Up to July 13, 2020, more than 12 million laboratory-confirmed cases of COVID-19 infection have been reported worldwide, 1,864,681 in Brazil. We aimed to assess an intervention to deal with the impact of the COVID19 pandemic on the operations of a rapid response team (RRT). Initial assessment An observational study with medical record review, was carried out at a large tertiary care hospital in Fortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Other studies on healthcare workers perspectives to the government response to COVID-19 stated that appropriate infection prevention measures were adopted during the pandemic, like systematic or streamlined supply and use of PPE, and adoption of prevention guidelines ( 43 , 44 ). We observed that in one-third of cases, trained RRTs consisting of health professionals was present in their country while two-third opined the presence of structured use of reporting system, similar to other studies ( 45 47 ). The preparedness for the reorganization of the health system in preventing the magnitude of COVID-19 has helped in containing the outbreak through a rapid increase in bed capacity, adequate equipment and staffing, triaging mechanism, and safe delivery of primary care services which is contrary to the current study which scored below average ( 48 50 ).…”
Section: Discussionsupporting
confidence: 88%
“…Other studies on healthcare workers perspectives to the government response to COVID-19 stated that appropriate infection prevention measures were adopted during the pandemic, like systematic or streamlined supply and use of PPE, and adoption of prevention guidelines ( 43 , 44 ). We observed that in one-third of cases, trained RRTs consisting of health professionals was present in their country while two-third opined the presence of structured use of reporting system, similar to other studies ( 45 47 ). The preparedness for the reorganization of the health system in preventing the magnitude of COVID-19 has helped in containing the outbreak through a rapid increase in bed capacity, adequate equipment and staffing, triaging mechanism, and safe delivery of primary care services which is contrary to the current study which scored below average ( 48 50 ).…”
Section: Discussionsupporting
confidence: 88%
“…We interviewed 3 nurses (2 quality and safety and 1 informatics specialists). Key themes were: (1) participants perceived the dashboard as a facilitator for auditing NEWS2 recording and escalation of care to improve clinicians practice; (2) There is a need for guiding clinicians and adjusting data sources and metrics which could enhance the functionality and usability. From EHR (2019 to 2022) data analysis showed: (1) NEWS2 recording has gradually improved in the implementation and evaluation phases (May 2021 to Apr 2022) from 64% to 83%; (2) Referral and nurses’ assessment forms completion increased (n: 170 to 6800 & 23 to 540, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The Covid 19 pandemic has taken its toll on health care services globally. The escalating pressure has significantly raised the surge in deteriorating patients and the need to escalate their care (1). There was an increase in daily tasks for nurses, physicians and rapid response teams to cope with the COVID-19 strain (1).…”
Section: Introductionmentioning
confidence: 99%
“…Another observational study reviewing medical records was conducted at a hospital in Fortaleza, Brazil in 2020. [38] A total of 15,461 RRT calls were made during the study period. Since the outbreak of the pandemic, the number of cases treated has risen by an average of 30.6 daily calls to 79.2, while the extremely critical cases have increased from 3.5 to 22.…”
Section: Covid-19mentioning
confidence: 99%